Arte Visive 2 : Giovani artisti dal concorso nazionale. - Fochessati, Matteo; Palazzo Ducale, Genova (Genova : Corigraf, 1998)
Arena, Francesco ; Arzenton, Michele ; Barbera, Simona ; Bertarini, Corrado ; Bizzari, Rocco ; Boldrin, Massimo ; Bolmini, Marina ; Borrelli, Mimmo ; Campi, Thomas ; Cantiello, Teresa ; Cattani, Annalisa ; et al.
Palazzo Ducale, Genova, 3 ottobre - 15 novembre 1998
kunstcatalogus